Manifestations of mental existence in syntactic categories - Ali Jasib Abdulallah / Kadhim Jabar Alaq ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The research bases on the concept of manifestation of mental existence in various syntatic categories to elaborate the sort of bonds between concept of existence and the typical of syntactic thinking. Such understanding predict the influence of the concept upon the embedded cognitive systems of mental syntactic and perceive the scope of syntatic rules forming , rooting the grammar rules and wording the basis of syntactic theory.